Variations in reproductive strategy of the silver Arowana, Osteoglossum bicirrhosum Cuvier, 1829 from four sub‐basins of the Peruvian Amazon. (December 2015) - Duponchelle, F.; Ruiz Arce, A.; Waty, A.; Garcia‐Vasquez, A.; Renno, J.‐F.; Chu‐Koo, F.; Garcia‐Davila, C.; Vargas, G.; Tello, S.; Ortiz, A.; Pinedo, R.; Manzanares Vásquez, R.; et al.
Summary: The aim of this study was to assess the variability of reproductive characteristics of the silver Arowana, Osteoglossum bicirrhosum, in four sub‐basins of the Peruvian Amazon: the Amazonas, Ucayali, Napo and Putumayo rivers. An illustrated, detailed gonadal maturation scale is proposed for a clearer determination of the reproductive status of male and female Arowana. The breeding season occurred during the dry season and early rising waters in the Amazonas and Ucayali, whereas it was restricted to the dry season in the Napo and Putumayo. A same female can reproduce more than once during the breeding season. Age at maturity was reached during the second year, at sizes varying between 43–45 cm for males and 46–50 cm SL for females. Important variations in fecundity were observed between fish of the four sub‐basins, whereas mean oocytes diameter and mass did not vary significantly, suggesting differences in reproductive investment. Together with previously reported variations of growth patterns in the same sub‐basins, these results suggest the existence of distinct populations in the Peruvian Amazon, with important consequences for management and conservation, but also for future aquaculture development programs.